Pengukuran Kinerja Manajemen Rantai Pasokan dengan SCOR Model 9.0 (Studi Kasus di PT Indocement Tunggal Prakarsa Tbk) - Mutakin, Anas; Hubeis, Musa (Jurnal Manajemen dan Organisasi, 2011)
The objectives of this research were (1) Assess the supply chain structure of cement products in PT Indocement Induk Prakarsa (ITP) Tbk; (2) Conduct performance measurement of supply chain management (SCM) for cement products in PT ITP Tbk approach Supply Chain Operations Reference (SCOR) model version 9.0; (3) Provide alternatives solution to the problem after the measurement is known along with suggestions of measurement and analysis activities of SCM at PT ITP Tbk. Calculation of performance metrics level 1 is the perfect order fulfillment (POF) 82.43%, order fulfillment cycle time (OFCT) 2 days, the cost of good sold (COGS) 53.84% and cash-to-cash cycle time (CTCCT) 53 days. Opportunity value that is calculated using the lost opportunity measure (LOM) is a POF registration COGS Rp 552,146,310,636 and Rp 127,956,658,590. The mapping level 2 shows PT ITP Tbk have performance lowest deliver process, because the expedition and transportation of cement is less effective and efficient in sending customer orders. Mapping level 3 shows in detail the process of delivering PT ITP Tbk, so it can answer why deliver a low performance. From the results of the overall SCM performance PT ITP Tbk good enough, but needs to be improved on the expedition and the distribution of transportation to reach the target business objectives set PT ITP Tbk, which is improving customer service and increase profits.